Day length predicts investment in human immune function: Shorter days yield greater investment. (September 2019) - Gassen, Jeffrey; Proffitt Leyva, Randi P.; Mengelkoch, Summer; White, Jordon D.; Peterman, Julia L.; Prokosch, Marjorie L.; Bradshaw, Hannah K.; Eimerbrink, Micah J.; Corrigan, Emily K.; Cheek, Dennis J.; Boehm, Gary W.; Hill, Sarah E.
Highlights: We found seasonal changes in multiple measures of human immune function. Specifically, shorter photoperiods predicted more robust immune responses. In men, these changes were accompanied by decreased levels of total testosterone. These results have key practical implications for researchers and clinicians. Abstract: Winter is characterized by stressful conditions which compromise health and render animals more vulnerable to infection and illness than during other times of the year. Organisms are hypothesized to adapt to these seasonal stressors by increasing investment in immune function in response to diminished photoperiod duration. Here, we examined this hypothesis in a sample of healthy human participants. Using several functional immune assays in vitro, as well as by utilizing measures of in vivo proinflammatory cytokine levels, we predicted that shorter day length would be associated with greater investment in immunological function. Results revealed that shorter days predicted significant upregulation of several facets of immune function, including natural killer cell cytotoxicity, peripheral blood mononuclear cell proliferation (in response to, and in the absence of stimulation), and plasma levels of interleukin-6, as well as lower rates of Staphylococcus aureus growth in serum ex vivo . Further, consistent with the hypothesis that these trade-offs would be offset by decreased investment in mating effort, shorter day length also predicted lower levels of total testosterone in men. These results suggest that ambient photoperiod may be a powerful regulator of human immunological activity, providing some of the first evidence of seasonal changes in multiple facets of human immune function.